The information and support needs of primary caregivers of premature and/or medically complex infants upon discharge from the neonatal intensive care unit. - Aylward, Deborah Ann. (University of Ottawa (Canada), 2002)
Objective. To determine the perceptions of primary caregivers of premature and/or medically complex infants regarding information received prior to discharge from hospital and information and support needs four weeks after discharge from a Neonatal Intensive Care Unit (NICU). Design. Non-experimental descriptive design with administration of two questionnaires prior to and four weeks after discharge. Demographic information was collected prior to discharge. Setting. Prior to discharge, the NICU of a regional pediatric teaching hospital and four weeks after discharge, the home environment. Participants. Thirty of thirty-two (94%) consecutively discharged primary caregivers of premature and/or medically complex infants enrolled over a four-month period. Results. Information related to basic infant care was perceived to have been provided. Information related to infant environment, behaviour and development, the unique characteristics of premature infants and recognition of changes in infant's health status require more attention. Written information and a number of a place to call for information were wanted. Conclusions. Primary caregivers indicate the need for reinforcement of information provided in hospital once they are at home, especially in the area of infant behaviour and development and characteristics specific to the premature infant. This is relevant to program planning and a method to deliver and/or reinforce this information should be developed.
Keywords: Health Sciences, Nursing.